How does intellectual capital affect product innovation performance?: evidence from China and India - Zhang, Min; Qi, Yinan; Wang, Zhiqiang; Pawar, Kulwant S.; Zhao, Xiande (Emerald, 2018)
Purpose: Intellectual capital reflects the sum of existing knowledge a manufacturer is able to leverage and plays a critical role in new product development. This study aims to empirically investigate the mechanisms through which intellectual capital enhances product innovation performance and how economic and institutional environments affect the mechanisms. Design/methodology/approach: Using a knowledge-based view and institutional theory, this study proposes a model on the relationships among intellectual capital, supplier knowledge integration, supply chain adaptability, and product innovation performance. The hypotheses are empirically tested using multiple group structural equation modelling and data collected from 300 Chinese and 200 Indian manufacturers. Findings: We find that intellectual capital improves product innovation performance both directly and indirectly through supplier knowledge integration. However, the effects are different in China and India. In particular, the direct effect of intellectual capital on product innovation performance is significantly higher in China than that in India, and intellectual capital improves product innovation performance indirectly through supplier knowledge integration only in India. We also find that supplier knowledge integration improves product innovation performance indirectly through supply chain adaptability in both China and India. Originality/value: Using a moderated mediation model, this study provides insights into the joint effects of intellectual capital, supplier knowledge integration, and supply chain adaptability on product innovation performance. The findings enhance current understandings of how supply chain management helps a manufacturer develop new products using existing knowledge and the influences of economic and institutional environments on knowledge and supply chain management.